The mindfulness-based stress reduction program for improving sleep quality in cancer survivors: A systematic review and meta-analysis. (March 2021) - Suh, Hyo-Weon; Jeong, Ha Yeong; Hong, Sunggyu; Kim, Jong Woo; Yoon, Seong Woo; Lee, Jee Young; Chung, Sun-Yong
Highlights: Cancer survivors commonly suffer from sleep disturbance. Mindfulness-based stress reduction (MBSR) is widely used for cancer survivors. MBSR is more likely to increase sleep quality than usual care. There is no significance between MBSR and cognitive behavior therapy for insomnia. Given the cost and resource, MBSR is a promising option for cancer survivors. Abstract: Introduction: This study aims to evaluate the efficacy and effectiveness of a mindfulness-based stress reduction (MBSR) program in improving sleep in cancer survivors. Methods: Four electronic databases (Cochrane Library, EMBASE, PubMed, and PsycARTICLES) were searched for randomized controlled trials evaluating the effects of MBSR on the sleep of cancer survivors from their inception to May 2020. The primary outcome was sleep quality measured by validated questionnaires such as the Insomnia Severity Index and Pittsburgh Sleep Quality Index. The secondary outcomes were sleep parameters obtained from a sleep diary, polysomnography, and actigraphy. The included studies were critically appraised by the Cochrane risk of bias tool and meta-analyzed. Results: Ten studies were included, and nine studies were analyzed quantitatively. MBSR significantly improved sleep quality compared to usual care (standardized mean difference −0.29, 95 % confidence interval −0.55 to −0.04, I 2 = 58 %). However, there were no favorable results with sleep parameters. Compared to active controls, MBSR presented mixed results with sleep quality according to the outcomes and negative results with sleep parameters. Conclusion: This review suggests that MBSR helps cancer survivors improve sleep quality. Our results support the possibility of using MBSR for cancer survivors. However, its efficacy and effectiveness in improving sleep quality and sleep parameters are inconclusive because the number of included studies was few with inconsistent results. Further studies with high methodological quality are required to establish conclusive evidence about the efficacy and effectiveness of MBSR in improving sleep quality and sleep parameters in cancer survivors.